Employers as Subjects of the Immigration State: How the State Foments Employment Insecurity for Temporary Immigrant Workers. Issue 1 (1st February 2021) - Gleeson, Shannon; Griffith, Kati L.
Abstract: The state plays a key role in shaping worker precarity, and employers are key actors in mediating this process. While employers sometimes may act as willing extensions of the deportation machinery, they are also subjects of the immigration state. In this article, we highlight the impact of state-employer dynamics on migrant workers with Temporary Protected Status (TPS). These workers have only provisional permission to live and work in the United States, but are not tied to any single employer. Even though they are privileged over unauthorized workers and employer-sponsored guest workers, TPS holders experience their own brand of state-induced precarity. Their employers risk civil or criminal liability if they are not in compliance with work authorization requirements and must repeatedly navigate an unpredictable and confusing immigration bureaucracy. Drawing on interviews with 121 low-wage TPS workers and two dozen of their advocates in the New York City metropolitan area, our findings reveal that the intertwined coercive and bureaucratic arms of the immigration state together make hiring TPS workers a more risky and costly proposition for employers, thereby exacerbating the job insecurity that TPS workers already face due to an at-will employment regime that offers few protections against firing.